C Catappa Dip Addition on Betta Fish (Betta sp) Color Change - Kristiana, Indra; Astiyani, Wahyu Puji; Reza Maulana, Reza; Aditya, Ega; Pietoyo, Atiek (Program Studi Akuakultur, Universitas Bangka Belitung, 2023)
Betta fish, one of freshwater ornamental fish aquaculture commodities which has high sale value. Betta fish has various pattern and unique fish fin shape. Cattapa dip was a fish health product consisting of catappa leaves and vitamin C. This product could be use for betta fish cultivation so as not to be attacked by parasites, fungi, bacteria and also for helping the process of betta fish color changing. Cattapa dip could also maintain the stability of the water pH in betta fish cultivation. This product has a shape resembling a tea bag product which is very attractive and unique. This study consisted of 4 treatments and 3 replications. The treatments given were Treatment A (0.3 gram of catappa leaves and 0.1 gram vitamin C), Treatment B (0.5 gram of catappa leaves and 0.1 gram of vitamin C), Treatment C (0.7 gram of catappa leaves and 0.1 gram of vitamin C) and K treatment / control (without treatment). The parameter observed during the study was the color change of Betta fish (Betta sp) which was measured by the percentage of color change based on RGB (Red Green Blue) using the Color Picker application. The results showed that the treatment with the addition of Kataplus in the form of dip as much as 0.5 gram of ketapang leaves and 0.1 gram of vitamin C was the best treatment. Based on the results of the color changes that occur in treatments A, B, C with 3 color indicators namely Green (green), Red (red), and Blue (blue). Color changes occurred in weeks 1st to week 4th where the best were obtained in treatment B with the average percentage produced, namely Red of 125,975%, Green of 111,375% and Blue of 116,6%. So it could be conclude that the use of Cattapa dip has an effect on color changes in Betta fish (Betta sp).